1982
DOI: 10.1002/app.1982.070271105
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and studies of phosphorus‐containing polyurethane foams based on tetrakis(hydroxymethyl) phosphonium chloride derivatives

Abstract: synopsisA phosphorus-and nitrogen-containing polyol is prepared by condensing tetrakis(hydrox ymethy1)phosphonium chloride with diethanol amine in aqueous medium. The newly synthesized p o l y o l -b i s ( h y d r o x y m e t h y l ) -~~-b i a ( 2 -h y~~e t h y l )~o m e~y l p h~p~eoxide (-0) is used in the preparation of rigid polyurethane foams with a various phosphorus content. With the view to comparing their properties, polyurethane foams are also prepared on the basis of the commercially available flame … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 7 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…In general, reactive-type flame retardants are mostly based on halogens and phosphorus. Recently, selected halogen-containing flame retardants have been banned because they have poor environmental profiles, along with some human health and toxicity effects. For this reason, there is a strong desire to develop effective nonhalogenated flame retardants with superior environmental profiles and the ability to react with foams and not leach into the environment. , It has been widely demonstrated that the most suitable reactive flame retardants for rigid polyurethane foams are mainly phosphorus-containing polyols, such as 2,2′-((bis(hydroxymethyl) phosphoryl)methylazanediyl)diethanol, tris(dipropylene glycol)phosphonate, diethyl- N , N ′-bis(2-hydroxyethyl)aminomethylphosphonate, diethyl- N , N ′-diethanolaminomethylphosphate, and morpholinophosphoryldimethanol. ,, Several new phosphorus-containing polyols, based on tetrakis(hydroxymethyl)phosphonium chloride (THPC), have been used for rigid polyurethane foams, being introduced into the polyurethane main chain in the chain-extension step. , Moreover, the modified rigid polyurethane foams showed good flame resistance. Usually, these phosphorus-containing polyols are used as chain extenders or reactive monomers for rigid polyurethane foams; however, they are rarely used for FPUF.…”
Section: Introductionmentioning
confidence: 99%
“…In general, reactive-type flame retardants are mostly based on halogens and phosphorus. Recently, selected halogen-containing flame retardants have been banned because they have poor environmental profiles, along with some human health and toxicity effects. For this reason, there is a strong desire to develop effective nonhalogenated flame retardants with superior environmental profiles and the ability to react with foams and not leach into the environment. , It has been widely demonstrated that the most suitable reactive flame retardants for rigid polyurethane foams are mainly phosphorus-containing polyols, such as 2,2′-((bis(hydroxymethyl) phosphoryl)methylazanediyl)diethanol, tris(dipropylene glycol)phosphonate, diethyl- N , N ′-bis(2-hydroxyethyl)aminomethylphosphonate, diethyl- N , N ′-diethanolaminomethylphosphate, and morpholinophosphoryldimethanol. ,, Several new phosphorus-containing polyols, based on tetrakis(hydroxymethyl)phosphonium chloride (THPC), have been used for rigid polyurethane foams, being introduced into the polyurethane main chain in the chain-extension step. , Moreover, the modified rigid polyurethane foams showed good flame resistance. Usually, these phosphorus-containing polyols are used as chain extenders or reactive monomers for rigid polyurethane foams; however, they are rarely used for FPUF.…”
Section: Introductionmentioning
confidence: 99%
“… 14 22 A phosphorus-containing organic compound, diethyl bis(2-hydroxyethyl) aminomethylphosphonate (DBAMP), has attracted intensive attention due to its high rate of performance and price. 23 Silicone flame retardants not only endow EP with excellent flame retardancy but also improve the processing properties, heat resistance, and so on. In addition, they do not release toxic gas during combustion.…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly because the products of phosphorous compounds decomposed by heat have a very strong dehydrating effect, which can make the surface of the covered polymer carbonized, form the char layer to isolate the air, and thus play the role as a condensation phase flame retardant. At present, phosphorus-containing organic compounds of various structures have been reported as flame retardants for EP. A phosphorus-containing organic compound, diethyl bis­(2-hydroxyethyl) aminomethylphosphonate (DBAMP), has attracted intensive attention due to its high rate of performance and price . Silicone flame retardants not only endow EP with excellent flame retardancy but also improve the processing properties, heat resistance, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Flame retardant polyurethane foams were prepared by modification with phosphorus-and nitrogencontaining polyols 25 . Tertiary polyfunctional amines (containing hydroxyl, thiol and amino groups), with alkyl, cycloalkyl and phenyl radicals were used for polyurethane stabilisation 26 .…”
Section: Introductionmentioning
confidence: 99%